1999
DOI: 10.1210/jc.84.7.2373
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Growth Hormone (GH) Replacement in Men with Childhood-Onset GH Deficiency

Abstract: Short term GH replacement therapy has been shown to improve body composition and exercise capacity. It is not yet known whether GH replacement remains beneficial over the long term. We assessed the effects of long term GH replacement on body composition, bone mineral density, and cardiac function. Thirty-eight men with childhood-onset GH deficiency were studied for a period of 3-5 yr. Measurements included anthropometry, computed tomographic scanning of abdomen and upper leg, bone densitometry, echo cardiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 0 publications
6
84
0
3
Order By: Relevance
“…The cardiac hypertropy may be transient, since it subsides after 2 years of continuous treatment, but improvements in cardiac performance persist for up to 10 years (Ter Maaten et al 1999). Other studies using AOGHD patients (Nass et al 1995) did not observe any improvement in cardiac morphology or function following GH treatment.…”
Section: Metabolic Disturbancesmentioning
confidence: 90%
See 1 more Smart Citation
“…The cardiac hypertropy may be transient, since it subsides after 2 years of continuous treatment, but improvements in cardiac performance persist for up to 10 years (Ter Maaten et al 1999). Other studies using AOGHD patients (Nass et al 1995) did not observe any improvement in cardiac morphology or function following GH treatment.…”
Section: Metabolic Disturbancesmentioning
confidence: 90%
“…GH replacement increases ventricular mass and/or performance in COGHD patients (Amato et al 1993, Sartorio et al 1997, Ter Maaten et al 1999. The cardiac hypertropy may be transient, since it subsides after 2 years of continuous treatment, but improvements in cardiac performance persist for up to 10 years (Ter Maaten et al 1999).…”
Section: Metabolic Disturbancesmentioning
confidence: 99%
“…During 38 months of GH replacement therapy, cardiac structure was normalized, whereas heart rate and cardiac index increased to supernormal levels (34). In 38 young men with childhood-onset GHD followed openly for 55 (range 39-69) months, GH replacement increased stroke volume and maximal exercise capacity without any long-term increase in left ventricular mass (35). In seven adults with adult-onset GHD, 42 months of GH replacement increased left ventricular mass and decreased the atrial emptying index, which reflects diastolic function, as compared with healthy matched controls (36).…”
Section: The Heartmentioning
confidence: 99%
“…Ample and robust evidence supports the remedial effects of GH replacement on body composition, including gradual normalization of lean body mass (LBM) and reduction in fat mass (10,11). A number of studies have also demonstrated improvements in psychological well-being, with specific improvements in energy, emotional reactions and social isolation (12,13).…”
Section: Introductionmentioning
confidence: 99%